Estimasi Pergerakan Aliran Barang Komoditi Pangan Kabupaten Klaten Ke Wilayah Di Jawa Tengah: Estimation Of The Flow Of Food Commodity Goods In Klaten District To The District In Central Java - Herna Puji Astutik (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Klaten area has extensive agricultural land, there are still rice fields and food industrial areas. There are many small and large-scale food industries in Klaten Regency whose travel patterns have not been identified. Where these industries are the driving force for the economy of several regions in Klaten Regency, of course, there must be a travel identification policy set. In the stages of determining a policy or decision, there is a need for data that must be available and complete, such as traffic data and information. Traffic data serves as material for determining traffic policies for various regions, which are used to identify opportunities for demand for goods traffic. This transport policy increases traffic as a form of intervention on the delivery side of the road network. This study uses a quantitative descriptive method and data collection method with the Secondary Data Analysis (ADS) approach. The secondary data used in this study is survey data, namely the Ministry of Transportation, the Transportation Research and Development Agency, Surveys of Origin, and Destination of Goods Transportation. The results of the analysis show that the volume of food cargo transported from Klaten Regency to all Regencies in Central Java is 548,605 tons per month in 2023, the largest food commodities are rice and coffee, followed by agricultural commodities and grains. The largest mode of cargo transportation from Klaten Regency to areas in Central Java is to the Boyolali Regency, Sukoharjo Regency, and Magelang Regencies